Preparation method of container lining bag for powder transportation
By using a mixed and extruded film formation technology in the lining bag in the container, combined with the design of the waterproof weaving layer, forming an inner lining bag with anti -static, moisture -proof, impact resistance and tensile stretching, solve the powder body, which solves the powder body, which solves the powder body. The problem of reduced sealing effects and moisture absorption in product transportation extends the life of the inner lining bag.
Patent Information
- Application Number
- CN202411942847.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When transporting powder products, existing container lining bags are prone to reduce the sealing effect due to impact, pulling, static electricity and other reasons, and powder substances are prone to leakage or moisture absorption, affecting quality.
The preparation method of lining bag in the container for powder transportation is adopted, and mixes and mixes the Mao metamin, linear low -density polyethylene, antistatic particles, anti -static fiber, tougin agent and other materials The film, combined with the design of the waterproof weaving layer, forms a fitting structure of the inner lining layer and the waterproof weaving layer. Through the heat sealing forming, it forms an anti -static, moisture -proof, impact and tensile -resistant end lining bag.
It has achieved good moisture -proof, anti -static, impact resistance and tensile stretchability in the process of transporting powder products, extending the service life of the inner lining bag, avoiding the leakage and suction of the powder substances. Tide problem.
Smart Images

Figure CN119369788A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of processing and manufacturing of transport packaging parts, and more specifically, it relates to a method for preparing a container liner bag for powder transportation. Background Art
[0002] Container liner bags, also known as container dry material bags, can not only transport solid bulk particles and powdered products, but also package liquid products. Due to containerized transportation, compared with traditional woven bag packaging and ton bag transportation methods, they have the advantages of large unit transport volume, easy loading and unloading, reduced labor, and no secondary pollution of goods.
[0003] When transporting solid products, existing containers are prone to affecting the sealing effect of the liner bags due to impact and collision between particles during transportation, as well as pulling of the liner bags during loading, which can easily cause leakage of goods inside the liner bags. In addition, during the transportation of food powders, plastic particles and other materials, they need to have good waterproof and moisture-proof effects to ensure that the powder materials are not easy to absorb moisture and affect their own quality. During the transportation of powders and plastic powder particles in a dry environment, static electricity is easily generated due to friction, which causes the powder particles to be easily adsorbed on the surface of the liner bags, affecting the unloading efficiency of the powder materials.
[0004] Therefore, how to prepare a new container liner bag so that the liner bag has good moisture resistance, antistatic properties, impact resistance and tensile resistance during the transportation of powder is a problem to be solved. Summary of the invention
[0005] In order to prepare a new container liner bag, so that the liner bag has good moisture resistance, antistatic properties, impact resistance and tensile resistance during the transportation of powder, the present application provides a method for preparing a container liner bag for powder transportation.
[0006] In the first aspect, the present application provides a method for preparing a container liner bag for powder transportation, which adopts the following technical solution: A method for preparing a container liner bag for powder transportation comprises the following steps: S1, weighing metallocene polyethylene, linear low-density polyethylene, and toughening agent, mixing and stirring evenly to obtain a primary mixture; then adding antistatic particles, antistatic fibers, antistatic lubricants, compatibilizers, and antioxidants, mixing and stirring evenly to obtain a mixture; the mixture is melt-extruded into a film to obtain an inner lining layer (4); S2, spraying the shellac compound liquid evenly on one side of the woven fabric, spraying 50-100 mL of the shellac compound liquid evenly per square meter of the woven fabric, and drying to obtain a waterproof woven fabric layer (5); S3, laminating the inner lining layer (4) and the waterproof woven fabric layer (5) on the side without the shellac composite liquid, and then cutting and heat-sealing and forming the inner lining bag (1).
[0007] By adopting the above technical scheme, the surface of the waterproof woven cloth layer is attached with a shellac compound liquid. After drying, the shellac compound liquid forms a shellac film, which has a good moisture-proof effect, so that the waterproof woven layer has a good moisture-proof effect; and in combination with the woven cloth layer, the strength and tensile strength can be guaranteed, so that the liner bag is not easy to tear when the staff pulls the liner bag; after the liner layer contacts with the loaded powder items, due to the moisture-proof effect of the external waterproof woven cloth layer, the liner layer is not easy to absorb external moisture, and the loaded powder particles remain in a dry state, and the powder particles are easily produced by mutual collision under dry conditions. Static electricity is generated, and the antistatic effect of antistatic particles, antistatic fibers, and antistatic lubricants is used to prevent powder particles from adhering to the inner lining due to static electricity, thereby affecting the unloading efficiency and the accuracy of the transportation volume; antistatic particles, antistatic fibers, toughening agents, and compatibilizers are used to further improve the impact resistance and tensile resistance of the inner lining. In the process of transporting granular materials, when there is an impact environment such as sudden braking, the inner lining can buffer the impact of the particles and ensure the integrity of the inner lining. Problems such as impact cracks and impact holes are not likely to occur, ensuring that the container liner bags have a long service life during the powder transportation process.
[0008] Preferably, the inner lining layer (4) comprises the following raw materials in parts by weight: 30-60 parts of metallocene polyethylene, 20-40 parts of linear low-density polyethylene, 10-25 parts of antistatic particles, 5-10 parts of antistatic fibers, 5-10 parts of toughening agent, 1-2 parts of antistatic lubricant, 10-20 parts of compatibilizer, and 1-2 parts of antioxidant; the antistatic particles are composed of lauramide particles, nitrogen-doped carbon nanotubes, and chitosan quaternary ammonium salt particles in a mass ratio of 1:1-2:1-3.
[0009] By adopting the above technical solution, the melting point of lauramide particles is about 100°C. After hot melting, lauramide has lubricating fluidity, which can reduce the friction effect between the powder particles and the lining layer and prevent static electricity. Even if static electricity is generated, the positive charge in the chitosan quaternary ammonium salt particles is convenient for neutralizing the negative charge generated by friction. The static electricity on the surface of the lining bag is reduced by offsetting the static electricity. The nitrogen-doped carbon nanotubes gradually change the electronic structure as nitrogen atoms are doped in the carbon nanotubes, promote the appearance of holes in the carbon nanotubes, and further increase the conductive effect of the nitrogen-doped carbon nanotubes, thereby further improving the antistatic effect of the lining layer and preventing the powder particles from adhering to the surface of the lining layer.
[0010] The amide group in the lauramide particles is hydrophilic, and the amino group in the chitosan quaternary ammonium salt particles is also hydrophilic. The waterproof woven fabric layer blocks the moisture from the external environment, so that the lining layer can adsorb excess moisture between the powder particles and during the powder injection process. The surface of the lining layer carries a small amount of water molecules, which can prevent the accumulation of charge. The conductive effect is used to improve the antistatic effect of the surface of the lining layer. Combined with the conductive effect of nitrogen-doped carbon nanotubes, it further promotes the uniform dispersion of charges, reduces static electricity accumulation, and further improves the antistatic effect.
[0011] Preferably, the lauramide particles are made of lauramide liquid and zirconium silicide particles in a mass ratio of 1:0.1-0.3.
[0012] By adopting the above technical scheme, lauramide liquid and zirconium silicide particles are matched, and the lauramide liquid adheres to the surface of the zirconium silicide particles. The good lubricating effect of the surface of the lauramide liquid is utilized, and it is not easy to generate static charge due to friction. The conductive effect of zirconium silicide is combined to further promote the uniform conduction of static charge, reduce the local static charge accumulation, and ensure that the surface of the inner lining layer has a good antistatic effect; at the same time, lauramide can improve the internal structure and stress distribution of polyethylene, and combined with the higher strength of zirconium silicide, further increase the impact strength and tensile strength of the inner lining layer.
[0013] Preferably, the nitrogen-doped carbon nanotubes are prepared by vapor deposition of carbon nanotubes in urea solution under nitrogen protection conditions.
[0014] By adopting the above technical scheme, urea is deposited in the hollow structure of the carbon nanotubes and on the surface of the carbon nanotubes during the vapor deposition process. Nitrogen doping can regulate the energy band structure of the carbon nanotubes, increase their carrier concentration, and thus improve their electrical conductivity. Nitrogen doping can also induce the formation of electron-rich reduction active centers on the surface of the carbon nanotubes, which not only increases the surface area of the nitrogen-doped carbon nanotubes, but also increases the electrical conductivity, further improving the antistatic effect of the nitrogen-doped carbon nanotubes, so that the finished lining layer has a better antistatic effect.
[0015] Preferably, the chitosan quaternary ammonium salt particles are made of chitosan quaternary ammonium salt solution and SBS particles in a mass ratio of 1:0.1-0.3.
[0016] By adopting the above technical scheme, chitosan quaternary ammonium salt solution and SBS particles are combined, and the good impact toughness of SBS particles and the good antistatic effect of chitosan quaternary ammonium salt are utilized, so that the powder impacting the surface of the inner lining layer is not easily adsorbed on the surface of the inner lining layer due to impact friction, thereby ensuring the antistatic effect of the inner lining layer, preventing powder adhesion, and ensuring unloading efficiency.
[0017] Preferably, the antistatic fiber is made of carbon fiber, silver fiber and polyethylene glycol liquid in a mass ratio of 1:0.1-0.3:0.5-1.
[0018] By adopting the above technical scheme, carbon fiber, silver fiber and polyethylene glycol liquid are matched, and the good bonding effect of polyethylene glycol liquid is utilized to adhere to the surface of carbon fiber and silver fiber, and the hydroxyl group in polyethylene glycol is easy to attract and connect with the amino group in chitosan quaternary ammonium salt particles and the amide group in lauramide particles, so as to realize the connection and contact between antistatic particles and antistatic fibers. When static charge is generated, the conductive effect of antistatic fibers and antistatic particles is utilized to realize a conductive network inside the inner lining layer, so as to prevent static charge from gathering and accumulating, thereby ensuring the antistatic effect of the inner lining layer.
[0019] Preferably, the toughening agent is made of polyethyleneimine liquid and POE in a mass ratio of 1:1-3.
[0020] By adopting the above technical scheme, the polyethyleneimine liquid utilizes its good bonding effect to adhere to the POE surface, and the amino groups in the polyethyleneimine are easy to attract and connect with the hydroxyl groups on the surface of the antistatic fiber, thereby promoting the distribution of POE and polyethyleneimine near the antistatic fiber and antistatic particles. The good flexibility and impact resistance of POE and polyethyleneimine are utilized, combined with the tensile strength of carbon fiber and silver fiber, to further improve the impact resistance and tensile resistance of the inner lining layer, and extend the service life of the inner lining layer.
[0021] Preferably, the antistatic lubricant consists of polyethylene wax and polyethylene glycol 4000 in a mass ratio of 1:1-2.
[0022] By adopting the above technical solution, polyethylene wax and polyethylene glycol 4000 are combined to utilize their lubricating effect to reduce the amount of static charge generated, so that the surface of the inner lining layer has better antistatic lubricity, and can improve the impact resistance and tensile strength of the inner lining layer.
[0023] Preferably, the compatibilizer is composed of maleic anhydride grafted polyethylene, maleic anhydride grafted POE and maleic anhydride grafted SBS in a mass ratio of 1:1-2:1-2.
[0024] By adopting the above technical solution, the bonding density between the antistatic particles and the polyethylene is improved, thereby improving the impact resistance and tensile strength of the inner lining layer.
[0025] Preferably, the waterproof woven fabric layer is made by uniformly spraying a shellac composite liquid on the surface of the woven fabric, and the shellac composite liquid is made of a shellac solution and an ethyl cellulose solution in a mass ratio of 1:0.5-1.
[0026] By adopting the above technical scheme, the shellac solution and the ethyl cellulose solution have good moisture-proof effect. When the shellac composite liquid is sprayed onto the surface of the woven cloth, the waterproof and moisture-proof effect of the waterproof woven cloth layer is improved, ensuring that the powder loaded inside the liner bag is not easily affected by the external environment and absorbs moisture, thereby ensuring the transportation effect of the powder; at the same time, the shellac solution and the ethyl cellulose solution adhere to the surface of the woven cloth, which can further improve the strength of the waterproof woven cloth layer and extend the service life of the liner bag.
[0027] In summary, this application has the following beneficial effects: 1. The inner lining layer has good anti-static and anti-impact effects. Combined with the waterproof woven cloth layer, it improves the moisture resistance and tensile resistance of the inner lining bag, making the inner lining bag have a longer service life.
[0028] 2. The combination of nitrogen-doped carbon nanotubes and chitosan quaternary ammonium salt particles, the doping of nitrogen atoms will introduce additional electrons or holes, thereby changing the Fermi level and electronic state density of graphene, improving the electrostatic transmission effect of the antistatic network, and preventing static charge aggregation; chitosan quaternary ammonium salt particles are positively charged, when friction generates negatively charged static charges, the positive and negative charges on the surface of the chitosan quaternary ammonium salt particles offset each other, further reducing the accumulation of static charges, and improving the friction static electricity of the lining layer during the transportation of powder particles.
[0029] 3. Prepare the inner lining layer first, and then prepare the waterproof woven cloth layer. After the inner lining layer and the waterproof woven cloth layer are laminated and heat-sealed, the inner lining layer and the waterproof woven cloth layer are tightly bonded to ensure the strength and impact resistance of the inner lining bag. After the inner lining bag prepared by heat-sealing molding has a feed port and a discharge port, the remaining gaps are tightly bonded to ensure the moisture-proof effect. At the same time, the contact between the inner lining bag and the powder particles can prevent the powder particles from being adsorbed on the surface of the inner lining bag due to static electricity. It also has good tensile resistance and impact resistance to ensure the service life of the inner lining bag. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is the front view of the liner bag; Figure 2 is a cross-sectional view of the liner bag; In the figure: 1. liner bag; 2. feed port; 3. discharge port; 4. liner layer; 5. waterproof woven fabric layer. DETAILED DESCRIPTION
[0031] The present application is further described in detail below with reference to the embodiments. Preparation Example of Lauramide Granules
[0032] The lauramide in the following raw materials was purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.; the other raw materials were all commercially available.
[0033] Preparation Example 1: Lauramide particles are prepared by the following method: 1 kg of lauramide liquid is evenly sprayed on the surface of 0.3 kg of zirconium silicide particles, and after drying and dispersion, finished lauramide particles are obtained; the lauramide liquid is a 5% by mass lauramide ethanol solution, the mass fraction of ethanol is 99%, and the average particle size of the zirconium silicide particles is 5 μm.
[0034] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 1 kg of lauramide liquid was evenly sprayed on the surface of 0.1 kg of zirconium silicide particles, and after drying and dispersion, finished lauramide particles were obtained. Preparation example of nitrogen-doped carbon nanotubes
[0035] The following raw materials are commonly available in the market.
[0036] Preparation Example 3: Nitrogen-doped carbon nanotubes were prepared by the following method: 1 kg of carbon nanotubes were immersed in 10 kg of urea solution, ultrasonically dispersed at 20 kHz for 10 minutes, then 8 kg of urea solution was poured out, and heated to 950 ° C at a heating rate of 10 ° C / min for 6 hours under the condition of nitrogen passing, cooled to room temperature and dispersed to obtain finished nitrogen-doped carbon nanotubes; the average length of the carbon nanotubes was 10 μm, and the urea solution was a 10% urea aqueous solution. Preparation Example of Chitosan Quaternary Ammonium Salt Granules
[0037] The chitosan quaternary ammonium salt in the following raw materials was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; other raw materials are commonly available on the market.
[0038] Preparation Example 4: Chitosan quaternary ammonium salt particles were prepared by the following method: 1 kg of chitosan quaternary ammonium salt solution was uniformly sprayed onto the surface of 0.2 kg of SBS particles, and the finished chitosan particles were obtained after drying and dispersion; the chitosan quaternary ammonium salt solution was a chitosan quaternary ammonium salt aqueous solution with a mass fraction of 3%, and the average particle size of the SBS particles was 20 μm.
[0039] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 1 kg of chitosan quaternary ammonium salt solution was uniformly sprayed onto the surface of 0.1 kg of SBS particles, and the finished chitosan particles were obtained after drying and dispersion.
[0040] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 1 kg of chitosan quaternary ammonium salt solution was uniformly sprayed onto the surface of 0.3 kg of SBS particles, and the finished chitosan particles were obtained after drying and dispersion. Preparation example of antistatic fiber
[0041] The following raw materials are all commercially available.
[0042] Preparation Example 7: Antistatic fiber is prepared by the following method: 0.8 kg of polyethylene glycol liquid was evenly sprayed on the surface of 1 kg of carbon fiber and 0.2 kg of silver fiber, and the finished antistatic fiber was obtained after drying and dispersion until the fibers were not sticky and agglomerated with each other; the average length of the carbon fiber was 8 μm, the average length of the silver fiber was 10 μm, the polyethylene glycol liquid was a polyethylene glycol aqueous solution with a mass fraction of 10%, and the polyethylene glycol was polyethylene glycol 8000.
[0043] Preparation Example 8: This preparation example differs from Preparation Example 7 in that: 0.5 kg of polyethylene glycol solution was evenly sprayed on the surface of 1 kg of carbon fiber and 0.1 kg of silver fiber, and the finished antistatic fiber was obtained after drying and dispersion until the fibers were not adhered to each other and agglomerated.
[0044] Preparation Example 9: This preparation example differs from Preparation Example 7 in that: 1 kg of polyethylene glycol solution was evenly sprayed on the surface of 1 kg of carbon fiber and 0.3 kg of silver fiber, and the finished antistatic fiber was obtained after drying and dispersion until the fibers were not adhered to each other and agglomerated. Preparation example of toughening agent
[0045] Among the following raw materials, POE was purchased from Shanghai Oushuo Plastic Co., Ltd., brand 8450; polyethyleneimine was purchased from Shandong New Kinetic Energy Chemical Co., Ltd.
[0046] Preparation Example 10: The toughening agent is prepared by the following method: 1 kg of polyethyleneimine liquid was evenly sprayed on the surface of 2 kg of POE, and the finished toughening agent was obtained after drying and dispersion until POE did not stick to each other and agglomerate; the average particle size of POE was 20 μm.
[0047] Preparation Example 11: This preparation example differs from Preparation Example 10 in that: 1 kg of polyethyleneimine liquid was evenly sprayed on the surface of 1 kg of POE, and the finished toughening agent was obtained by drying and dispersing until the POE did not stick to each other and agglomerate.
[0048] Preparation Example 12: This preparation example differs from Preparation Example 10 in that: 1 kg of polyethyleneimine liquid was evenly sprayed on the surface of 3 kg of POE, and the finished toughening agent was obtained by drying and dispersing until the POE did not stick to each other and agglomerate. Example
[0049] The following raw materials are all commercially available.
[0050] Example 1: A container liner bag for powder transportation: It comprises a waterproof woven layer 5 and an inner lining layer 4; In the inner lining 4: 50kg of metallocene polyethylene, 30kg of linear low-density polyethylene, 20kg of antistatic particles, 8kg of antistatic fiber, 8kg of toughening agent, 2kg of antistatic lubricant, 15kg of compatibilizer, and 2kg of antioxidant; the antistatic particles are composed of lauramide particles prepared in Preparation Example 1, nitrogen-doped carbon nanotubes prepared in Preparation Example 3, and chitosan quaternary ammonium salt particles prepared in Preparation Example 4 in a mass ratio of 1:1.5:2; the antistatic fiber is the antistatic fiber prepared in Preparation Example 7, and the toughening agent is the antistatic fiber prepared in Preparation Example 10; the antistatic lubricant is composed of polyethylene wax and polyethylene glycol 4000 in a mass ratio of 1:1; the compatibilizer is composed of maleic anhydride grafted polyethylene, maleic anhydride grafted POE, and maleic anhydride grafted SBS in a mass ratio of 1:1:1; the antioxidant is antioxidant 1010; The preparation method is as follows: S1, weighing metallocene polyethylene, linear low-density polyethylene, and toughening agent, mixing and stirring evenly to obtain a primary mixture; then adding antistatic particles, antistatic fibers, antistatic lubricants, compatibilizers, and antioxidants, mixing and stirring evenly to obtain a mixture; the mixture is melt-extruded at 190° C. to form a film to obtain an inner lining layer 4; the average thickness of the inner lining layer 4 is 30 μm; S2. Mix and stir 1 kg of shellac solution and 1 kg of ethyl cellulose solution to obtain a shellac composite solution, wherein the shellac solution is a 5% by mass ethanol solution of shellac, the ethyl cellulose solution is a 2% by mass ethanol solution of ethyl cellulose, and the mass fraction of ethanol is 99%; spray the shellac composite solution evenly on the surface of one side of the woven fabric, the woven fabric is a polyethylene woven fabric, and 80 mL of the shellac composite solution is evenly sprayed per square meter of the woven fabric, and dried to obtain a waterproof woven fabric layer; the average thickness of the waterproof woven fabric layer is 40 μm; S3, the inner lining layer 4 is laminated to the side of the waterproof woven cloth layer without the shellac compound liquid, and then cut and heat-sealed at 190° C. After heat-sealing, except for the feed port and the discharge port, the remaining positions are bonded and laminated to form the inner lining bag 1.
[0051] Embodiment 2: This embodiment differs from Embodiment 1 in that: In the inner lining layer 4: 30kg of metallocene polyethylene, 20kg of linear low-density polyethylene, 10kg of antistatic particles, 5kg of antistatic fiber, 5kg of toughening agent, 1kg of antistatic lubricant, 10kg of compatibilizer, and 1kg of antioxidant; the antistatic particles are composed of lauramide particles prepared in Preparation Example 2, nitrogen-doped carbon nanotubes prepared in Preparation Example 3, and chitosan quaternary ammonium salt particles prepared in Preparation Example 5 in a mass ratio of 1:1:1; the antistatic fiber is the antistatic fiber prepared in Preparation Example 8, and the toughening agent is the antistatic fiber prepared in Preparation Example 11; the antistatic lubricant is composed of polyethylene wax and polyethylene glycol 4000 in a mass ratio of 1:1.
[0052] Embodiment 3: This embodiment differs from Embodiment 1 in that: In the inner lining 4: 60kg of metallocene polyethylene, 40kg of linear low-density polyethylene, 25kg of antistatic particles, 10kg of antistatic fiber, 10kg of toughening agent, 2kg of antistatic lubricant, 20kg of compatibilizer, and 2kg of antioxidant; the antistatic particles are composed of lauramide particles prepared in Preparation Example 1, nitrogen-doped carbon nanotubes prepared in Preparation Example 3, and chitosan quaternary ammonium salt particles prepared in Preparation Example 6 in a mass ratio of 1:2:3; the antistatic fiber is the antistatic fiber prepared in Preparation Example 9, and the toughening agent is the antistatic fiber prepared in Preparation Example 12; the antistatic lubricant is composed of polyethylene wax and polyethylene glycol 4000 in a mass ratio of 1:2; the compatibilizer is composed of maleic anhydride grafted polyethylene, maleic anhydride grafted POE, and maleic anhydride grafted SBS in a mass ratio of 1:2:2.
[0053] Embodiment 4: This embodiment differs from Embodiment 1 in that: In the preparation process of the lauramide particles in the antistatic particles, no zirconium silicide particles are added, only lauramide particles are present, and the average particle size of the lauramide particles is 20 μm.
[0054] Embodiment 5: This embodiment differs from Embodiment 1 in that: No SBS particles were added in the preparation process of the chitosan quaternary ammonium salt particles in the antistatic particles, only chitosan quaternary ammonium salt powder particles were present, and the average particle size of the chitosan quaternary ammonium salt powder particles was 10 μm.
[0055] Embodiment 6: This embodiment differs from Embodiment 1 in that: The antistatic fiber is carbon fiber.
[0056] Embodiment 7: This embodiment differs from Embodiment 1 in that: The toughening agent is POE. Comparative Example
[0057] Comparative Example 1: The difference between this comparative example and Example 1 is that: Replace the waterproof woven fabric layer 5 with a polyethylene woven fabric of equal quality.
[0058] Comparative Example 2: The difference between this comparative example and Example 1 is that: No antistatic particles, antistatic fibers and antistatic lubricants are added to the raw materials.
[0059] Comparative Example 3: The difference between this embodiment and embodiment 1 is that: No lauramide particles and chitosan quaternary ammonium salt particles are added to the antistatic particles.
[0060] Comparative Example 4: The difference between this embodiment and embodiment 1 is that: The nitrogen-doped carbon nanotubes are replaced by carbon nanotubes of equal mass in the antistatic particles. Performance testing 1. Moisture resistance test
[0061] The inner liner bag 1 was prepared by the methods of Examples 1-3 and Comparative Example 1 respectively. The inner liner bag 1 was filled with dried silica gel desiccant in an amount of 50%. The weight of the silica gel desiccant was recorded as the initial weight. After the feed port 2 and the discharge port 3 of the inner liner bag were closed, the inner liner bag 1 was placed in an environment with a relative humidity of 95% for 3 days, and then the discharge port 3 was opened to take out all the silica gel desiccant. The weight of the silica gel desiccant was weighed and recorded as the treated weight. The weight difference = treated weight - initial weight was calculated. The larger the weight difference, the higher the moisture absorption capacity and the worse the moisture resistance of the inner liner bag 1. 2. Antistatic testing
[0062] The methods of Examples 1-3, 6-7 and Comparative Examples 2-4 were respectively used to prepare an inner liner bag 1, in which polypropylene particles were loaded at a loading amount of 95%, and the loading amount was recorded; the inner liner bag 1 loaded with polypropylene particles was placed on a vibration table and vibrated at 2000 Hz for 60 minutes to simulate the vibration of the inner liner bag 1 during transportation, and then the discharge port 3 was opened to pour out the polypropylene particles, the inner liner bag 1 was cut open, and the polypropylene particles attached to the surface of the inner liner bag 1 were recorded, and the greater the attachment amount, the greater the static electricity. 3. Impact resistance test
[0063] The liner bag 1 was prepared by the methods of Examples 1-7 and Comparative Example 4, and the liner layer on the liner bag 1 was repeatedly impacted 430 times with an impact force of 20N at a distance of 10cm. The tensile strength was tested with reference to GB / T10454-2000 and the data was recorded. 4. Stretch resistance test
[0064] The liner bag 1 was prepared by the methods of Examples 1-7 and Comparative Example 4, and the tensile strength was tested with reference to GB / T10454-2000, and the data was recorded.
[0065] Table 1 Performance test table (“ / ” in the table means that the corresponding embodiment or comparative example did not test the item, so there is no data)
[0066] It can be seen from Examples 1-3 and Table 1 that the liner bag 1 prepared in the present application has good waterproof and moisture-proof properties, good antistatic effect, and good impact resistance and tensile resistance.
[0067] It can be seen from Example 1 and Examples 4-7 and Table 1 that no zirconium silicide particles were added during the preparation of the lauramide particles in the antistatic particles of Example 4. Compared with Example 1, the tensile strength of the liner bag 1 prepared in Example 4 without impact and after 30 impacts is less than that of Example 1, indicating that the zirconium silicide particles can increase the impact resistance and tensile strength of the liner bag 1.
[0068] No SBS particles were added during the preparation of the chitosan quaternary ammonium salt particles in the antistatic particles of Example 5. Compared with Example 1, the tensile strength of the liner bag 1 prepared in Example 5 was lower than that in Example 1, indicating that the SBS particles have good toughness and impact resistance, and can enhance the impact resistance and tensile strength of the liner bag 1.
[0069] The antistatic fiber of Example 6 is carbon fiber. Compared with Example 1, the adhesion amount of the liner bag 1 prepared in Example 6 is greater than that of Example 1, and the tensile strength is slightly lower than that of Example 1; this indicates that the presence of polyethylene glycol can improve the antistatic effect and the impact resistance of the liner bag 1.
[0070] The toughening agent in Example 7 is POE. Compared with Example 1, the adhesion amount of the liner bag 1 prepared in Example 7 is greater than that in Example 1, and the tensile strength is less than that in Example 1; this indicates that polyethyleneimine has good toughness and good antistatic effect, and can improve the impact resistance and antistatic effect of the liner bag 1.
[0071] Combining Example 1 and Comparative Examples 1-4 and Table 1, it can be seen that Comparative Example 1 replaces the waterproof woven cloth layer 5 with a polyethylene woven cloth of equal mass. Compared with Example 1, the liner bag 1 prepared in Comparative Example 1 has poorer waterproof and moisture resistance than Example 1; this indicates that the addition of the shellac composite liquid can further block moisture from the external environment, ensure that the internal powder is in a dry state during transportation, and is not easy to absorb moisture and affect the quality of the transported goods.
[0072] No antistatic particles, antistatic fibers and antistatic lubricants were added to the raw materials of Comparative Example 2. Compared with Example 1, the antistatic effect of the liner bag 1 prepared in Comparative Example 2 was worse than that in Example 1. This indicates that the antistatic particles, antistatic fibers and antistatic lubricants cooperate with each other to prevent charge generation, charge aggregation and charge conduction, thereby further reducing the electrostatic adsorption inside the liner bag 1, thereby ensuring that the liner bag 1 has a good antistatic effect and is not easy to affect the unloading rate.
[0073] No lauramide particles and chitosan quaternary ammonium salt particles are added to the antistatic particles in Comparative Example 3. Compared with Example 1, the adhesion amount of the liner bag 1 prepared in Comparative Example 3 is greater than that in Example 1. This indicates that the combination of lauramide particles and chitosan quaternary ammonium salt particles can achieve an antistatic effect by charge offset, thereby ensuring the antistatic effect of the liner bag 1.
[0074] In Comparative Example 4, the antistatic particles are replaced with nitrogen-doped carbon nanotubes with the same mass of carbon nanotubes. Compared with Example 1, the attachment amount of the liner bag 1 prepared in Comparative Example 4 is greater than that in Example 1, and the tensile strength is less than that in Example 1; this indicates that the nitrogen-doped carbon nanotubes can improve the antistatic effect and the tensile strength of the liner bag 1. After 30 impacts, the strength loss value is small, indicating that it has a better impact resistance.
[0075] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A method for preparing a container liner bag for powder transportation, characterized in that: The steps include: S1, weighing metallocene polyethylene, linear low-density polyethylene, and toughening agent, mixing and stirring evenly to obtain a primary mixture; then adding antistatic particles, antistatic fibers, antistatic lubricants, compatibilizers, and antioxidants, mixing and stirring evenly to obtain a mixture; the mixture is melt-extruded into a film to obtain an inner lining layer (4); S2, spraying the shellac compound liquid evenly on one side of the woven fabric, spraying 50-100 mL of the shellac compound liquid evenly per square meter of the woven fabric, and drying to obtain a waterproof woven fabric layer (5); S3, laminating the inner lining layer (4) and the waterproof woven fabric layer (5) on the side without the shellac composite liquid, and then cutting and heat-sealing and forming the inner lining bag (1).
2. The method for preparing a container liner bag for powder transportation according to claim 1, characterized in that: The inner lining layer (4) comprises the following raw materials in parts by weight: 30-60 parts of metallocene polyethylene, 20-40 parts of linear low-density polyethylene, 10-25 parts of antistatic particles, 5-10 parts of antistatic fibers, 5-10 parts of toughening agent, 1-2 parts of antistatic lubricant, 10-20 parts of compatibilizer, and 1-2 parts of antioxidant; the antistatic particles are composed of lauramide particles, nitrogen-doped carbon nanotubes, and chitosan quaternary ammonium salt particles in a mass ratio of 1:1-2:1-3.
3. The method for preparing a container liner bag for powder transportation according to claim 2, characterized in that: The lauramide particles are made of lauramide liquid and zirconium silicide particles in a mass ratio of 1:0.1-0.
3.
4. The method for preparing a container liner bag for powder transportation according to claim 2, characterized in that: The nitrogen-doped carbon nanotubes are prepared by vapor deposition of carbon nanotubes in urea solution under nitrogen protection conditions.
5. The method for preparing a container liner bag for powder transportation according to claim 2, characterized in that: The chitosan quaternary ammonium salt particles are prepared from a chitosan quaternary ammonium salt solution and SBS particles in a mass ratio of 1:0.1-0.
3.
6. The method for preparing a container liner bag for powder transportation according to claim 1, characterized in that: The antistatic fiber is made of carbon fiber, silver fiber and polyethylene glycol liquid in a mass ratio of 1:0.1-0.3:0.5-1.
7. The method for preparing a container liner bag for powder transportation according to claim 1, characterized in that: The toughening agent is made of polyethyleneimine liquid and POE in a mass ratio of 1:1-3.
8. The method for preparing a container liner bag for powder transportation according to claim 1, characterized in that: The antistatic lubricant consists of polyethylene wax and polyethylene glycol 4000 in a mass ratio of 1:1-2.
9. The method for preparing a container liner bag for powder transportation according to claim 1, characterized in that: The compatibilizer consists of maleic anhydride grafted polyethylene, maleic anhydride grafted POE and maleic anhydride grafted SBS in a mass ratio of 1:1-2:1-2.
10. The method for preparing a container liner bag for powder transportation according to claim 1, characterized in that: The shellac composite liquid is prepared from a shellac solution and an ethyl cellulose solution in a mass ratio of 1:0.5-1.
Citation Information
Patent Citations
Integrated process for producing paper-plastic compound bags by recycling waste plastics
CN102344008A
Antistatic threads for plastic woven bags
CN103628171A
Production process of plastic woven bag
CN105109052A
Flexible containers and methods of forming the same
CN105705431A
High-strength antistatic polyethylene film as well as preparation method and application thereof
CN106432888A
Cited By
Efficient moisture-proof lining bag for container and preparation method of efficient moisture-proof lining bag
CN120756773A